The Impact of Living with Parkinson’s Disease: Balancing within a Web of Needs and Demands - Catharina Sjödahl Hammarlund; Albert Westergren; Ingrid Åström; Anna-Karin Edberg; Peter Hagell (Parkinson's Disease)
This study explores the impact of living with Parkinson’s disease (PD). Nineteen persons (11 women) aged 55–84 diagnosed with PD 3–27 years ago participated. Data were collected through semistructured interviews, which were recorded, transcribed verbatim, and analysed by qualitative content analysis. Four categories represented the impact of living with PD: “Changed prerequisites for managing day-to-day demands,” “Loss of identity and dignity,” “Compromised social participation,” and “The use of practical and psychological strategies.” There was a shift from an internal to an external locus of control in managing, control, competence, relatedness, and autonomy. According to self-determination theory, a shift towards extrinsically motivated behaviours may occur when these basic needs are thwarted, leading to compensatory strategies or needs substitutes with negative consequences on health and well-being. We suggest a needs-based approach as an important starting point to better understand the consequences of living with PD and to explore the means for people with PD to acquire an improved quality of life on their own terms. In conclusion, our findings suggest for a shift in focus, from a biomedical to a needs-based approach to understand the impact of living with PD and facilitate more person-centred care and person-centred outcome measurement.